THE CONTROL BOARD APPLIED TO UNIVERSITIES INTELLECTUAL CAPITAL MANAGEMENT (Costos y Gestión, 2020)
This paper purpose is to design a control board for an efficient management of the intellectual capital ofthe Economics Sciences Faculty, in Rio Cuartoʼs National University. For this, a descriptive study based on amodel designed for the identification and valuation of the intellectual capital in the university environmentwas used as starting point. The study was structured in components, variables, indicators, measurementguidelines and measurement tools. Traffic lights were used for the construction of the board because of their«visual condition», meaning that, through them, it is possible to visualize the current general situation of theindicators with only one look. The traffic light was made with Microsoft Excel. The results are the analysis andcontrol, periodically, of the indicators that present weaknesses with the possibility of being boosted throughtheir management, aiming more efficiency and future benefits, as well as those indicators producers of valuefor the institution, in a way to develop competitive advantages to achieve the differentiation of the EconomicsSciences Faculty of the Rio Cuartoʼs National University.
Keywords: Intellectual capital; School of Economics; Measurement; Management; Efficiency